Two-Stage Game-Based Pricing Strategy for the Duopoly Online Freight Platform. (19th April 2023) - Gu, Yong; Zhang, Wen; Su, Yuxia; Tang, Xin; Liao, T. Warren
Abstract : The online freight platform, also called freight resource sharing platform or freight O2O platform, developed rapidly lately, has gradually become the leaders in China's road freight market in recent years, especially in the intracity freight market. The platform's revenue mainly comes from the registration fee and commission, of which the commission is extracted from the freight rate. Therefore, how to determine the registration fee and freight rate becomes a key issue for the platform. Our research focuses on analyzing the pricing strategy by considering the charging mode, game model, and affecting factors. Based on the two-sided market theory and the classic Hotelling model, a tripartite game model of online freight platform-carrier-consignor is constructed. Furthermore, a game model of consignor and alternative carriers is built by introducing the platform user's psychological pressure and satisfaction priority into the model. Finally, through mathematical derivation and numerical experiment, we analyze the effects of various factors on platform profits, platform registration fees, and freight rate, and propose some suggestions to promote the orderly development of online freight platforms for the intracity freight market.